Effect of a Nurse-Led Protocol on Time to Treatment of Partial Occlusions in Central Venous Access Devices in Pediatric Oncology. (September 2020) - Hunter, Allison; Cunningham, K. Shantel; Yuen, Carol; Jensen, Kristen; Afzal, Arfan; Benzies, Karen
Central venous access devices (CVADs) are the standard of care in pediatric oncology. Occlusion is a common complication that can lead to delays in therapy, readmission, and CVAD removal and reinsertion. Early treatment of partial occlusions using a standardized protocol may restore patency and increase life span of CVADs. The objective of this study was to develop and evaluate a nurse-led protocol to manage partial CVAD occlusions in pediatric oncology and autologous bone marrow transplant patients. The protocol enabled nurses to manage partially occluded CVADs by administering thrombolytic therapy following an algorithm and patient-specific standing order. The primary outcome was time from recognition of the partial occlusion to instillation of a thrombolytic. Secondary outcomes were thrombolytic dwell time, number of complete occlusions, and CVAD life span. We used a quasi-experimental, after-only, nonequivalent control group design to compare patients not exposed (retrospective cohort, n = 137) and patients exposed (prospective cohort, n = 101) to the nurse-led protocol. Mann–Whitney U tests were used to compare time to treatment, dwell time, and CVAD life span between cohorts, and χ 2 was used to compare the proportion of occlusions classified as complete. Time to treatment was significantly lower in the prospective cohort ( M = 99.9 minutes) versus the retrospective cohort ( M = 483.7 minutes), U = 1366.50, p < .01, as was thrombolytic dwell time, U = 282.50, p < .01. Proportion of complete occlusions and CVAD life span did not differ between cohorts. The nurse-led protocol was effective to manage partial CVAD occlusions in pediatric oncology patients.